A new species of Favolaschia (Agaricales, Mycenaceae) from Yunnan Province, China - Lu, Wenhua; Chen, Xuemei; Kumla, Jaturong; Suwannarach, Nakarin; Elgorban, Abdallah M.; Dai, Dong-Qin; Tibpromma, Saowaluck; Karunarathna, Samantha C. (Phytotaxa, 2025)
During a survey of macro-fungi in Yunnan Province of China, two collections of Favolaschia on bamboo were collected from Fengping Town. These two Favolaschia collections were identified as a new species, namely Favolaschia variistipitata, and belonged to Favolaschia section Anechinus based on evidence of molecular phylogenetic analyses and morphological characteristics. The phylogenetic analyses were based on a combined ITS and LSU dataset, which indicated that the new species is a distinct taxon. Favolaschia variistipitata is characterized by white to greyish-white, gelatinous basidiomata with poroid hymenophore. A description, color photo plate of macro-morphology, line drawings of micromorphology, and phylogenetic tree to show the taxonomic placement of the new species are provided. Favolaschia variistipitata and its morphologically and phylogenetically closely related species are also discussed. Moreover, a comparison of the morphological features of Favolaschia species reported from China is provided, further highlighting the importance of this research.